Legal Consequences for Perpetrators of Beating Police Members on Duty - Muhammad Zulfikar; Amsori Amsori (Fakultas Hukum Dehasen, 2022)
Basically every member of the Police on duty in the field is required to be able to make decisions individually in dealing with real situations. Decision-making by the police involves issues of public order and security which are closely related to human rights. However, in the field, the task of the police, which is supposed to maintain order and protect the community, has actually been attacked and beaten, as in the example of the beating by one suspect for hitting the Head of Ops Ditlantas Polda Metro Jaya AKBP Karosekali..